Innovation of Learning Media: Developing a Car Air Conditioning Trainer to Improve Student Performance in Vocational Physics and Engineering - Afriwandi; Hasan Maksum; Rifdarmon; Eko Indrawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a mobile air conditioning (AC) trainer as an innovative learning medium to enhance students’ understanding, interest, and performance in automotive AC systems. The research adopted the Research and Development (R&D) approach using the 4D model, which consists of the Define, Design, Develop, and Disseminate stages. Validation was conducted by media and material experts, yielding Aiken’s V coefficients of 0.93 and 0.96, respectively, categorized as “Valid.” The practicality test involving teachers and students obtained mean scores of 94.20% and 96.24%, categorized as “Highly Practical.” The effectiveness of the developed trainer was evaluated through pretest and posttest data, resulting in an N-Gain score of 0.69, which indicates a “High” level of improvement. These findings demonstrate that the developed AC trainer is valid, practical, and effective as instructional media in vocational education, particularly in enhancing students’ academic achievement in automotive air conditioning systems.